Early results of a natural experiment evaluating the effects of a local minimum wage policy on the diet-related health of low-wage workers, 2018–2020 - Caitlin E Caspi; Maria Fernanda Gombi-Vaca; Julian Wolfson; Lisa J Harnack; Molly De Marco; Rebekah Pratt; Thomas Durfee; Samuel L. Myers (Public Health Nutrition, 2023)
Abstract